Assessment of quantitative and genetic molecular variation of Acacia karroo in two extreme populations - Bayonne Mboumba, Georges (Stellenbosch : University of Stellenbosch, 2008)
Thesis (MScConsEcol (Conservation Ecology and Entomology))--University of Stellenbosch, 2006.